PENGARUH IKLAN BERDASARKAN KONSEP AIDA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DALAM MEMBELI TIKET ASIAN GAMES TAHUN 2018 DI KOTA PALEMBANG - Yunita Risma Rusmasari; Mohamad Adam; Iyakrus Iyakrus; Marlina Widiyanti (The Manager Review, 2020)
The holding of the Asian Games multi sporting event is an Asian sports party which is held every 4 years and is participated by countries that are registered with the Olympic Council of Asia (OCA). This study aims to determine whether the advertising based on AIDA concept influence the purchase decision in purchasing Asian Games 2018’s tickets in Palembang. The data used in this study are primary data by distributing questionnaire to 100 respondents who was watching Asian Games 2018 in Palembang. The analysis technique used is multiple linear regression analysis that was previously tested for validity and reliability. The result obtained are attention, interest, desire and action have a positive and significant effect on purchase decision in purchasing Asian Games 2018’s tickets in Palembang. This research is expected to be a reference to choose which variable are better used in future studies. For event organizer to be able to pay attention more about advertising in order to do event more successfully.